Środowisko dziennikarskie w Łodzi w latach 1949–1956 - Mnich, Grzegorz (Acta Universitatis Lodziensis. Folia Historica, 2013)
This analysis of the journalistic community in Lodz pertains to the Stalinist period, years that were particularly difficult in journalism. The press was already being subjected to a Party apparatus that determined human resources policy as well as press content. Journalists were reduced to the role of a „transmission belt”, conveying and realizing the political line of the Party. A collective portrait of the Lodz press community has been made based on the biographies of 96 journalists and editors-in-chief who worked for the following Lodz daily newspapers in the period from 1949–1956: „Głos Robotniczy” (Workers’ Voice), „Dziennik Łódzki” (Lodz Daily), „Express Ilustrowany” (Express Illustrated) and, after the merger of a „readers” newspaper with a tabloid, „Łódzki Express Ilustrowany” (Lodz Express Illustrated). This group of almost 100 journalists is representative for the period of analysis, although certainly not complete. An analysis of the composition of the Lodz press corps from that period indicates significant changes in the journalistic community. There was a marked increase in the number of young employees, lacking professional education and experience in the profession, often from proletarian families. At the end of 1949, 65 people worked in the three Lodz newspapers, while in 1955 the number of all employed journalists in Lodz increased to 101. The greatest increase, almost double, in the number of staff was in the Party ranks. At the same time, journalists with pre-war credentials were dismissed from the job. Commitment to Party affairs became the most important criterion in the assessment of employees; professional preparation was less crucial. The article notes increased activity of the Lodz journalistic community during October of 1956: the Lodz press, following the example of Warsaw, demanded above all greater freedom of publication and the limitation and even lifting of censorship. The press also demanded that responsibility be given to the editor-in-chief and the board for the character of a newspaper and its circulation. The entire press community considered the reliability of publications and the acquisition of readers’ trust a matter of primary importance. The journalist was to advance from the role of an executor of imposed tasks to that of a social activist.